Petrography and mineralogy of rinded ferrous-carbonate concretions in the Middle Eocene carbonate rocks: A case study from the Avanah Formation in north-east Erbil City, northern Iraq - Asaad, Irfan Shaaban; Al-Juboury, Ali Ismail; Bal Akkoca, Dicle; Jha, Prakash (Wiley, 2022)
The spherical rinded concretions in the carbonate rocks of the Avanah Formation (Middle Eocene) in the Gomaspan section, north-east Erbil City, northern Iraq have been studied for the first time. They occur within the grey to yellow thick-bedded marly dolomitic limestone interbedded with thin beds of grey shale in the lower part of the formation. Their diameter varies between 1 and 3 cm, are mostly spherical in shape, and characterized by brownish to dark grey isopachous rinds or cortex and brownish-red centre. The microscopic study shows a similarity between the concretions and their host rocks in their microfacies and fossils contained. The main microfacies is dolomitized lime mudstone and contains Valvulina sp. and pelecypods. The concretions are affected by selective diagenesis that resulted in the colour changes between the centre and outer rims of the concretions. X-ray diffraction (XRD) analysis of concretions and host rocks revealed the presence of dolomite, calcite, quartz, illite and haematite, the latter exists only in the concretions. Meanwhile, the scanning electron microscopy (SEM) and EDX analyses supported the results of (XRD) and show that the iron oxide (haematite) mainly was concentrated in the outer orange to red cortex. While the dark black inner cortex is characterized by containing less amount of Fe as compared with Ca, O, C and Mg in addition to illite, which also exists in the carbonate host rocks. Field observations, petrographic and mineralogical analyses revealed that the studied concretions had undergone four stages of formation, which consequently include dissolution of semi-rounded fossils such as pelecypods and forming the moulds during the deposition of the carbonate rocks of the Avanah Formation, precipitation of calcite minerals in the moulds and formation of calcite concretions syn-depositionally, partial dolomitization of calcite in meteoric-marine mixed zone and formation of rinded iron oxide concretion by selective diagenesis in meteoric water conditions by the action of acidic water to form haematite.
Keywords: Avanah Formation; carbonate rocks; Middle Eocene; Northern Iraq; rinded iron oxide concretions